Pediatric sports specialization in elite ice hockey players - Black, S.; Black, K.; Dhawan, A.; Onks, C.; Seidenberg, P.; Silvis, M. (Sports Health: A Multidisciplinary Approach, 2019)
Background: Pediatric sports specialization, defined as intense year-round training in a single sport as a result of excluding other sports for more than 8 months per year, is common in the United States. There are demonstrated physical and social risks to early pediatric sports specialization (defined as before age 12 years). While thought to be needed to acquire appropriate experience and excel in a given sport, there remains little information on when athletes at the highest levels of their sport specialized. This study aimed to define when professional and collegiate ice hockey players specialized.